Cognitive Ability and Cardiovascular Control in Intellectually and Developmentally Disabled People - Kim, H.J.; Choi, M.H.; Lee, I.H.; Hong, S.P.; You, N.R.; Kim, H.S.; Lim, D.W.; Chung, S.C (Нейрофизиология, 2014)
Earlier, we examined positive effects of hyperoxic air on the cognitive ability of intellectually
and developmentally disabled people (IDDP). In this study, correlation between cognitive
performance in the visual matching task and heart rate (HR) was investigated under normal
air conditions. Eighteen men (mean age 28.7 ± 5.0 year) and 22 women (mean age 35.5 ± 6.9
year) with an assessed disability level of 2.3 ± 0.6 participated. The experiment consisted of
three phases, a total of 7 min, including the rest (3 min), control (2 min), and visual matching
task 2 min phases. The HR in visual matching task phase increased, compared to those in the
rest and control phases. The cognitive ability in the visual matching task correlated with the
HR values; the response time showed a negative correlation with HR, while the accuracy rate
showed a positive correlation. Thus, adaptive changes in cardiovascular regulation probably
related to cognitive efforts and emotional excitation should be considered a noticeable factor
influencing brain supply with oxygen in IDDP (similarly to healthy people). The result of this
study agrees with the earlier obtained indications that hyperoxic air can positively affect the
cognitive performance in IDDP. Раніше ми вивчали позитивні впливи повітря, збагаченого
киснем, на когнітивні здатності людей з недостатнім інтелектуальним розвитком (НІР). У нашій роботі ми досліджували кореляцію між показниками когнітивної активності в
тесті візуальної відповідності та частотою серцевих скорочень (ЧСС) у таких суб’єктів в умовах дихання нормальним
повітрям. У тестах брали участь 18 чоловіків (середній вік
28.7 ± 5.0 року) та 22 жінки (35.5 ± 6.9 року) з оцінкою рівня
інтелектуального розвитку 2.3 ± 0.6. Експеримент (загальна
тривалість 7 хв) складався з трьох фаз: стан розслаблення
(3 хв), контроль (2 хв) та тест візуальної відповідності
(2 хв). Величини ЧСС у межах цього тесту порівняно з величинами в умовах розслаблення й контролю зростали. Показники когнітивних здібностей корелювали з величинами
ЧСС; кореляція часу відповіді була негативною, а точності відповіді – позитивною. Отже, адаптивні зміни регуляції
серцево-судинної системи, мабуть, пов’язані з когнітивними
зусиллями та емоційним збудженням, є істотним фактором,
який впливає на постачання мозку киснем у людей із НІР
(як і у здорових людей). Результати нашої роботи узгоджуються з отриманими раніше свідоцтвами про те, що дихання
повітрям, збагаченим киснем, позитивно впливає на когнітивні можливості людей із НІР.